The mediating effect of psychological capital on the relationship between perceived social support and life satisfaction among Malaysian undergraduates - Nainee, Sarvarubini; Tan, Soon Aun; Tan, Chee Seng; Viapude, Glory Nancy (Universiti Malaysia Sabah, 2018)
Life satisfaction is a subjective assessment of the quality of one's life and it is vital to keep one’s life satisfaction in an optimum range. The hassles of life among young adults particularly undergraduates in this competitive era are overwhelming and may affect their satisfaction with life. Receiving care or assistance from his or her social network is one of the ways for an individual to cope with the challenges in life. Social support constitutes from different sources, including family, friends, and significant others (Mahanta & Aggarwal, 2013). Similar to receiving actual supports, perceived social support, one’s perception of the availability of supports, is also helpful to individuals. For instance, literatures indicate that perceived social support positively affects one’s adaptation and satisfaction towards life (Khan, 2015; Yeung & Fung, 2007). Although there has been growing literatures examining the influence of perceived social support towards life satisfaction, the mechanism on how social support influences one’s life satisfaction is still vague and received limited attention. To address the gap, the present study explored the role of psychological capital (PsyCap) in the relationship between perceived social support and life satisfaction. PsyCap reflects a person's positive state indexed by positive hope, sense of optimism, resilience, and self-efficacy. Empirical evidence shows that social support brings a positive impact on PsyCap (Li et al., 2014; Luthan, Avey, Avolio, & Peterson, 2010). On the other hand, components of PsyCap (e.g., hope) have also been found to have a positive relationship with life satisfaction (Caprara & Steca, 2005). As a result, we hypothesized that PsyCap mediates the linkage between perceived social support and life satisfaction. In this study, the samples were 285 undergraduates from both public and private universities in Malaysia. Participants responded to a set of questionnaire comprising Multidimensional Scale of Perceived Social Support (MSPSS), Compound Psychological Capital questionnaire (CPC) and Satisfaction with Life Scale (SWLS). Results indicated that the total effect of perceived social support on life satisfaction was statistically significant among undergraduates. The direct effect, upon controlling the effect of the mediator, was statistically significant. Furthermore, as assumed, the indirect effect of perceived social support on life satisfaction via PsyCap was found significant. This study implies that perceived social support is beneficial to elevate young adults’ PsyCap or internal assets which subsequently promote their life satisfaction. Our findings help expand the mushrooming body of research on the predictors of life satisfaction among undergraduates.